Medical Malpractice in Wuhan, China: A 10-Year Autopsy-Based Single-Center Study. Issue 45 (November 2015) - He, Fanggang; Li, Liliang; Bynum, Jennifer; Meng, Xiangzhi; Yan, Ping; Li, Ling; Liu, Liang
Abstract : Abstract: Medical disputes in China are historically poorly documented. In particular, autopsy-based evaluation and its impact on medical malpractice claims remain largely unstudied. This study aims to document autopsy findings and medical malpractice in one of the largest cities of China, Wuhan, located in Hubei Province. A total of 519 autopsies were performed by the Department of Forensic Medicine, Wuhan University School of Medicine, Wuhan, China, over a 10-year period between 2004 and 2013. Of these cases, 190 (36.6%) were associated with medical malpractice claims. Joint evaluation by forensic pathologists and clinicians confirmed that 97 (51.1%) of the 190 claims were approved medical malpractice cases. The percentage of approved malpractice cases increased with patient age and varied according to medical setting, physician specialty, and organ system. The clinico-pathological diagnostic discrepancy was significantly different among various physician specialties ( P = 0.031) and organ systems ( P = 0.000). Of those cases involved in malpractice claims, aortic dissection, coronary heart disease, and acute respiratory infection were most common. Association between incorrect diagnosis and malpractice was significant ( P = 0.001). This is the first report on China's medical malpractice and findings at autopsy which reflects the current state of health care services in one of the biggest cities in China.